Is Unbleached Cotton Better Than Bleached? Exploring the Limits of Life-Cycle Assessment in the Textile Sector. (October 2015) - Roos, Sandra; Posner, Stefan; Jönsson, Christina; Peters, Greg M.
The applicability of life-cycle assessment (LCA) for the textile industry is discussed with a special focus on environmental impact from chemicals. Together with issues of water depletion and energy use, the use of chemicals and their emissions are important environmental considerations for textile products. However, accounting for chemicals is a weak point in LCA methodology and practice. Two research questions were investigated in a case study of hospital garments: 1) whether LCA adds value to assessments of the chemical performance of textile products, and 2) whether inclusion of toxicity issues in LCA affects environmental performance rankings for textile products. It is concluded that the quantitative and holistic tool LCA is useful for environmental decision makers in the textile industry, and becomes more effective when chemical impacts are included. A flexible way forward is demonstrated to meet the challenge of accounting for chemicals in LCAs of textile products.